2005
DOI: 10.1892/0891-6640(2005)19[577:bmocii]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers of Cardiac Injury in Normal, Surviving Septic, or Nonsurviving Septic Neonatal Foals

Abstract: The cardiac biomarkers cardiac troponin T (cTnT) and I (cTnI) and the cardiac isoenzyme of creatine kinase (CKMB) are used extensively in human medicine to diagnose and provide valuable prognostic information in patients with ischemic, traumatic, and septic myocardial injury. We designed a study to establish normal values for these markers in healthy, neonatal foals and to compare them with values obtained from septic neonates in a referral hospital population. The 25th, 50th, 75th, and 95th percentiles for cT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…Foal survival in this study was approximately 67%, slightly higher than previously reported survival rates of 44.6% 32 and 61% 33 in similarly described septic foal groups treated at referral veterinary institutes. This survival rate is close to that of patients identified as having septic shock in human critical care 28 .…”
Section: Discussioncontrasting
confidence: 63%
“…Foal survival in this study was approximately 67%, slightly higher than previously reported survival rates of 44.6% 32 and 61% 33 in similarly described septic foal groups treated at referral veterinary institutes. This survival rate is close to that of patients identified as having septic shock in human critical care 28 .…”
Section: Discussioncontrasting
confidence: 63%
“…Increased cTnI concentrations have been identified in people with noncardiac diseases such as sepsis or septic shock, pulmonary embolism and chronic obstructive pulmonary disease . Similar findings have been reported in septic foals, calves with experimentally induced endotoxemia, laboratory animals after chemotherapy, dogs with renal failure and noncardiac systemic disease, gastric dilatation‐volvulus and in horses with surgical colic …”
supporting
confidence: 67%
“…Cardiac TnI concentration also correlated well with severity of disease and was associated with an adverse outcome in dogs with babesiosis . Increased cTnI and T concentrations also were observed in septic neonatal foals, but no significant difference was found between surviving and nonsurviving foals in that study …”
mentioning
confidence: 74%
“…Little work has been done to evaluate cTn levels during sepsis in veterinary medicine. A study involving septic foals showed that cTnT values were significantly elevated compared with healthy foals but there was no difference in levels among survivors compared with nonsurvivors 81 …”
Section: Infection and Inflammationmentioning
confidence: 99%